Rediseño e implementación de un proceso electro-hidráulico, usado en el laboratorío de control automático de la ESPOL, para controlar velocidad y presión mediante matlab-simulink y/o labview - Alarcón, J. (2009)
Electro-hydraulic process to be redesigned is the modification of a speed control plant called "Design and Implementation of a Speed Control System of a three-phase motor using Matlab”, in order to allow students to apply their knowledge in the field of Automatic Control on this system and become familiar with field equipment and control tools currently used in industry through of practices in the Automatic Control Laboratory of the Faculty of Electrical Engineering and Computer of ESPOL performed remotely, the objective is the development of an electro-hydraulic system which can perform control and monitoring variables: velocity and pressure in addition to the remote on and off of it, for which analyzed the changes and improvements that could be taken, as the use of a solenoid valve for entry of a disturbance, a transducer to measure pressure, the adequacy of the control circuit, using the cFP-2100 and modules for remote control and monitoring of signals, among others. For the analysis of the system and their respective control and use tools as MatLabR2007a and Labview 8.2.1.